2017
DOI: 10.1016/j.visres.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in human eye movements: An oculomotor signature?

Abstract: 2Human eye movements are stereotyped and repeatable, but how specific to a normal 3 individual are the quantitative properties of his or her eye movements? We recorded 4 saccades, anti-saccades and smooth-pursuit eye movements in a sample of over 1000 healthy 5 young adults. A randomly selected subsample (10%) of participants were re-tested on a 6 second occasion after a median interval of 18.8 days, allowing us to estimate reliabilities. 7Each of several derived measures, including latencies, accuracies, velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 70 publications
9
136
1
1
Order By: Relevance
“…However, even the earliest studies of fixation behaviour noted considerable individual differences 19,20 , and basic occulomotor traits vary reliably between observers [21][22][23][24][25][26] . Recent twinstudies revealed that social attention and gaze traces across complex scenes are highly heritable 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…However, even the earliest studies of fixation behaviour noted considerable individual differences 19,20 , and basic occulomotor traits vary reliably between observers [21][22][23][24][25][26] . Recent twinstudies revealed that social attention and gaze traces across complex scenes are highly heritable 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…saccade errors occurred in all groups more often during the presentation of food stimuli. In addition, the BED1 sample committed significantly more errors than the NWC sample, suggesting inhibitory control difficulties in the BED1 sample, which might be food-specific (see Schag et al, 2013a;Svaldi et al, 2014 (Bargary et al, 2017;Kissler & Keil, 2008;van Steenbergen, Band, & Hommel, 2011).…”
mentioning
confidence: 99%
“…In healthy persons, personal differences in oculomotor behavior are observed when looking at a monitor . Differences in eye movements in healthy individuals are referred as their “oculomotor signature.” Variations in gaze patterns during face‐to‐face communication have also recently been described …”
Section: Discussionmentioning
confidence: 87%
“…29,30 Differences in eye movements in healthy individuals are referred as their "oculomotor signature." 31 Variations in gaze patterns during face-to-face communication have also recently been described. 32 The arrow indicates the direction of gaze when a person looks at an object.…”
Section: Recent Developments In Eye Trackersmentioning
confidence: 99%